2008
DOI: 10.1152/ajpheart.00731.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase-derived hydrogen peroxide is a major endothelium-dependent relaxing factor

Abstract: Capettini LS, Cortes SF, Gomes MA, Silva GA, Pesquero JL, Lopes MJ, Teixeira MM, Lemos VS. Neuronal nitric oxide synthasederived hydrogen peroxide is a major endothelium-dependent relaxing factor. Am J Physiol Heart Circ Physiol 295: H2503-H2511, 2008. First published October 24, 2008 doi:10.1152/ajpheart.00731.2008.-Endothelium-dependent vasorelaxation in large vessels is mainly attributed to N -nitro-L-arginine methyl ester (L-NAME)-sensitive endothelial nitric oxide (NO) synthase (eNOS)-derived NO producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 62 publications
(74 reference statements)
6
54
0
9
Order By: Relevance
“…We found that all three NOS isoforms were expressed in HUVECs (Fig. 4A), similar to previously published data from several different groups (4,9,16). Interestingly, nNOS demonstrated a prominent nuclear localization, similar to the findings by several other groups (43,48), the significance of which in endothelial cells (such as on the regulation of protein expression) is currently being examined in our laboratory.…”
Section: E 2 Attenuates High Glucose-induced Nitrotyrosine and Peroxysupporting
confidence: 91%
See 2 more Smart Citations
“…We found that all three NOS isoforms were expressed in HUVECs (Fig. 4A), similar to previously published data from several different groups (4,9,16). Interestingly, nNOS demonstrated a prominent nuclear localization, similar to the findings by several other groups (43,48), the significance of which in endothelial cells (such as on the regulation of protein expression) is currently being examined in our laboratory.…”
Section: E 2 Attenuates High Glucose-induced Nitrotyrosine and Peroxysupporting
confidence: 91%
“…There is increasing evidence that nNOS exerts a beneficial effect under a number of inflammatory pathologies. Endothelial nNOS activity can have antiinflammatory and antiatherogenic effects, while nNOS-induced hydrogen peroxide can contribute to lowering of blood pressure (7,9,40). Given the emerging role for nNOS in maintaining cardiovascular health, any impairment of nNOS activity by E 2 under hyperglycemic conditions may actually worsen the cardiovascular outcome by making the vasculature more susceptible to inflammation and vasoconstriction despite offering some protection against glucose-induced peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can not exclude that it is also expressed in vasa nervorum considering recent report of the presence of nNOS in vascular endothelium (41). Note, that nNOS is constitutively expressed in some types of neurons, and can be induced in others (42).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, its effects are cell and context specific with arterial endothelial cells being generally more resistant to adverse effects than a number of other cell types. H 2 O 2 is also a major endothelial-derived hyperpolarizing factor (EDHF) mediating vasodilation by stimulation of a VSMC potassium channel (255,256). Nevertheless, ROS may promote activation of other pathways that interact with NF-B, such as the ASK1-JNK pathway as illustrated in FIGURE 5.…”
Section: General Ros Signaling Mechanismsmentioning
confidence: 99%